Combined impact of ROR2 and its ligands on the pathogenesis and prognosis of idiopathic pulmonary fibrosis - Park, Seung-Lee; Lee, Jong-Uk; Kim, Min Kyung; Seo, Eunjeong; Kim, Myung-Shin; Hwang, Hun Gyu; Kim, Jung Hyun; Chang, Hun Soo; Park, Choon-Sik (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2026)
Background and aim: Idiopathic pulmonary fibrosis (IPF) is a progressive interstitial lung disease characterized by aberrant fibroblast activation and extracellular matrix accumulation. Although ROR2 signaling via Wnt ligands has been implicated in fibrosis, their integrated clinical relevance in IPF remains unclear. This study investigated the clinical significance of ROR2 and its ligands—WNT1, WNT5A, and WNT7A—in IPF development and prognosis.Methods: Bronchoalveolar lavage (BAL) fluid was collected from 124 IPF patients and 17 controls. Protein levels of ROR2, WNT1, WNT5A, and WNT7A were measured using ELISA. Immunofluorescence staining was performed to evaluate cellular localization. Cox proportional hazards analysis with backward elimination was used to identify mortality risk factors. Kaplan–Meier and log-rank tests were used to compare cumulative mortality between subgroups.Results: The levels of ROR2 and WNT7A were significantly higher in IPF compared to controls (p < 0.001 and p = 0.030, respectively). Among the proteins analyzed (ROR2, WNT1, WNT5A, and WNT7A), only elevated ROR2 levels were independently associated with increased mortality (hazard ratio [HR] = 2.32, p = 0.026), whereas WNT1, WNT5A, and WNT7A did not show significant associations with survival after correction for multiple comparisons using the Benjamini–Hochberg false discovery rate (FDR) method. Immunofluorescence analysis demonstrated co-localization of ROR2 with COL1A1-positive fibroblasts, as well as with WNT1, WNT5A, and WNT7A. Exploratory stratification based on combined ROR2 and WNT5A expression identified a subgroup with low ROR2 / high WNT5A levels that showed a trend toward better prognosis.Conclusion: ROR2 levels in BAL fluid are independently associated with IPF pathogenesis and prognosis, and may serve as a useful biomarker for identifying molecular endotypes and assessing clinical risk. Exploratory findings suggest that ROR2 and its ligand may modulate prognosis in a subset of patients.